Peran Orang Tua dalam Pembentukan Nilai Karakter Anak Usia Dini melalui Metode Qashash al-Qur’an - Vita Fitriatul Ulya (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2020)
Parents have a very important role in developing the character of early childhood, because the family is the first and foremost educational environment for children. Early childhood is where children are in the age range of zero to six years and during this time the child is experiencing very rapid development. There are several methods that parents can do in instilling character values, one of which is by telling stories. Stories are considered effective because they remember the characteristics of young children who have a great curiosity, like to fantasize and imagine. The main character values ​​according to the Ministry of Education and Culture include integrity, nationalist, mutual cooperation, independent and religious values. The five characters can be taught by parents through learning the story of the Qur'an or Qashash al-Qur'an. Many stories in the Koran can be used as lessons and lessons, including the stories of previous Prophets, stories of people with good personalities not the Prophet's group and stories about events in the time of the Prophet. All the stories contained in the Koran can be used as lessons. Parents as the main and first teacher should tell these stories to children so that good character, personality or character is formed and they always become people who believe in God.